Children and young adults with anophthalmia and microphthalmia: Diagnosis and Management. Issue 8 (21st May 2020) - Taha Najim, Rezhna; Topa, Alexandra; Jugård, Ylva; Casslén, Beatrice; Odersjö, Marie; Andersson Grönlund, Marita
Abstract: Purpose: Congenital anophthalmia (A) and microphthalmia (M) are rare developmental defects, which could be isolated or syndromic. Our objective was to describe a cohort of children and young adults with A/M treated with ocular prosthesis, emphasizing clinical features, diagnosis, treatment, and follow‐up. Methods: Eighteen individuals (10 female) with unilateral A ( n = 3) and M ( n = 15) with a mean age of 9.5 years (range 0.8–31.8) and treated with ocular prosthesis were included. Data on medical history, clinical examinations and management of ocular prosthesis were collected. Genetic screening with microarray and whole‐exome sequencing targeting 121 A/M‐related genes was performed. Results: A/M appeared isolated (seven cases) or as part of a syndromic condition (11 cases). In 4/16 patients, mutations were detected in TFAP2A, CHD7, FOXE3 and BCOR ‐genes. In one patient, a possibly causal microdeletion 10q11 was shown. Associated ocular anomalies such as cataract and cysts were found in 16 (89%) of the A/M eyes, and in nine (50%) ophthalmological findings were found in the fellow eyes. The median ages at which the conformer and ocular prosthesis first were initiated were 7.8 months and 1.5 years. 16/17 patients fulfilled satisfactory orbital growth and cosmetic results when treated with ocular prosthesis from an early age. Conclusion: Based upon our findings, a multidisciplinary approach, including genetic assessment, is necessary to cover all aspects of A/M. Imaging, ultrasound and visual evoked potentials should be included. Early management is crucial for the outcome, in terms of non‐ocular findings, vision in the fellow eye, and for facial cosmetic development.